P181 IBD patients with early clinical and sonographic improvements achieve better long-term outcomes than patients with clinical improvements alone – one-year interim results of the TRUST BEYOND study. (21st January 2022) - Kucharzik, T; Helwig, U; Seibold, F; Biedermann, L; Högenauer, C; Fischer, I; Kolterer, S; Rath, S; Hammer, L; Maaser, C
Abstract: Background: In the treat-to-target era, frequent and objective monitoring of disease activity in IBD patients is emphasized [1]. Over the past years, intestinal ultrasound (IUS) has become a useful modality to monitor and assess disease activity and response to therapy. (Trans)mural response and healing examined by IUS have emerged as outcome measures of growing interest and potential therapeutic goals in the IBD community [2–4]. However, the predictive value of a composite clinical/IUS improvement for the long-term outcome remains elusive. Methods: TRUST BEYOND is an ongoing, prospective, observational, multi-centre study in patients with active CD or UC initiating a biologic- or Januskinase-inhibitor (JAKi)-therapy at baseline. The aim of this study is to assess the predictive value of IUS parameters evaluated at week 12 for the long-term outcome after 52 weeks (assessed by clinical+ sonographic endpoints). For this interim analysis, 89 IBD patients (39 CD, 50 UC) with a documented visit at week 52 until September were included. The predictive value of (trans)mural response (TR; reduction of ≥ 25% in bowel wall thickness, BWT) and clinical remission at W12 was evaluated for the outcome at W52. Results: Eighty-nine IBD patients in clinical flare with increased BWT were included into this analysis. Patients were predominantly female (53.9%, n=48) with a median age of 34.3 years (29.0–51.5) and a median disease duration of 7.18 years (2.31–13.47). Following the induction of advanced therapy, the rate of IBD patients with a (trans)mural response increased from 67.4% (n=60) at W12 to 73.0% (n=65) at W52. Likewise, the proportion of IBD patients demonstrating a (trans)mural healing rose from 32.6% (n=29) at W12 to 41.6% (n=37) at W52. Of note, 53.5% (n=38) of IBD patients who achieved the composite endpoint "clinical remission and (trans)mural response" at W12 were in clinical remission at W52 while only 23.9% of patients who were only in clinical remission at W12 sustained clinical remission until W52 (p=0.007). Moreover, patients achieving both early clinical remission and (trans)mural response had better sonographic outcomes at W52. Fig 1: W52 outcomes of patients with either clinical remission and (trans)mural response or only clinical remission at W12. Conclusion: IBD patients who reached the composite endpoint clinical remission and (trans)mural response at week 12 had better outcomes after 1 year compared to patients in early clinical remission only. Our results strongly suggest that it is worth treating patients to composite clinical and sonographic endpoints. Reference: 1. Turner D et al. Gastroenterol. 2021; 2 Kucharzik T et al. Clin Gastroenterol Hepatol. 2017; 3 Maaser C et al. Gut 2020; 4 Wilkens R et al. Therap Adv Gastroenterol 2021